BUKU POP UP DAN IMPLEMENTASINYA SEBAGAI SARANA MEDIA PENGEMBANGAN LITERASI ANAK USIA DINI BAGI GURU PAUD DI KABUPATEN BANYUMAS - Israhayu, Eko Sri; Fauzan, Akhmad; Fathonah, Siti (Ruang Kata, 2022)
A pop up book is a book with an embossed, two-dimensional or three-dimensional image display. Pop-up books can be used as a learning medium to develop literacy in early childhood. Based on a survey of 103 ECCE teachers in Banyumas District, data related to teachers' responses to the use of pop-up books was obtained. The data showed that respondents had an understanding that literacy recognition could be conveyed to learners through pop-up books. The basis for consideration of using pop up books can be used as a learning medium, because pop up books:(1) can be used to show the ability to recognize several symbols and signs including language (35%), (2) able to communicate learning messages with more concrete thoughts/ideas (65%). Respondents stated that pop up books can be used in learning activities, because pop up books can serve to support literacy: 1) reading literacy with the introduction of letters, words, and sentences (68.9%), 2) knowing stories (2%) and numeracy literacy, knowing numbers (29.1%). Although respondents mostly understand that pop-up books can be a learning medium to improve children's literacy, not many respondents have used them in learning activities. Based on respondents' answers, only 35% claimed to have used pop up books in learning activities, the remaining 65% of respondents admitted that they had never used pop up books in learning activities. Respondents who have not used pop up books, stated that it is not easy to find pop up books in bookstores. Another respondent stated that the price of pop up books is quite expensive, and hoped that the government would provide assistance in providing pop up book packages to schools. Keywords: pop up books, learning media, literacy